BERSEKUTU DALAM ALLAH TRITUNGGAL DIMULAI DALAM KEHIDUPAN KELUARGA KRISTIANI - Benny Suwito (Bahasa Indonesia, 2021)
Trinity is the root of Christian faith. People of God have a calling to embody it in their community. So that, this article would like to explain how the communion of the Holy Trinity can be initiated through the Christian family as the basic cell of community. It will analyse first the Holy Trinity as the origin of the Church for indicating the relationship between the Holy Trinity as the community and the Christian family as the miniature of the Church (ecclesia domestica). Afterward, it will demonstrate how the Christian family can endevour to live according to the spirit of the Holy Trinity and also how the Church seeks to its pastoral ministry to accompany the Christian family to be able to express her identity as the image of the Holy Trinity.